Applying the Chronic Care Model to Improve Patient Activation at a Nurse-Managed Student-Run Free Clinic for Medically Underserved People - Jason Saude DNP, APRN, FNP-BC; Mary L. Baker MSN, CNS, FNP-BC; Linnea M. Axman DrPH, MSN, FNP-BC, FAANP; Susan M. Swider PhD, PHNA-BC, FAAN (SAGE Publishing, 2020)
This article describes a practice change intended to improve patient activation, also described as self-care management, in a sample of uninsured and underinsured patients with one or more chronic diseases who received care at a nurse-managed student-run free clinic project. Chronic diseases are the leading causes of death and disability in the United States. Individuals with chronic illnesses may be uninsured or underinsured and often do not receive adequate medical management, resulting in complications and unnecessary hospitalizations. Lack of knowledge related to self-care has been identified as one risk factor associated with poor health outcomes in medically underserved populations. Student-run free clinics have emerged to provide care to groups that would otherwise not receive health care while simultaneously providing experiential learning for healthcare students. Guided by the Chronic Care Model, an intervention was designed to improve patients' self-care management and chronic disease care delivery offered by the family nurse practitioner and baccalaureate nursing students. The evaluation plan for the Patient Activation Intervention utilized a pretest-posttest design. The Patient Activation Measure tool was administered at the beginning and end of the intervention. Additional outcomes were evaluated using a chart audit tool. A total of 19 unique patients, representing 42 free clinic visits, were evaluated during the intervention period. The mean Patient Activation Measure score was 60.95 (standard deviation ± 12.03) and was indicative of a good foundational understanding of chronic illness and working toward self-management. Chi-square and Fischer's exact test statistics demonstrated a statistically significant ( p  <   .05) difference in the documentation of medication reconciliation, patient-centered goals, and self-management education from baseline to post intervention follow-up appointments. The evidence-based Patient Activation Intervention demonstrated promise as an effective method to increase patient's self-care management and improve patient-centered outcomes for underserved patients when delivered at a nurse-managed student-run free clinic.